Changes in Serum Concentrations of Bone Turnover Markers in Healthy Pregnant Women - Yiduo Zhang; Ruiying Li; Jing Zhang; Wenjie Zhou; Fan Yu (International Journal of Clinical Practice)
Background. Changes in bone metabolism during pregnancy have not received sufficient attention because of the lack of effective screening tools. Bone turnover markers (BTMs) could reflect the changes of bone metabolism. Currently, reference intervals for bone metabolism during normal pregnancy are inconclusive. This study aimed to determine reference intervals for BTMs in pregnant women taking prenatal care and to facilitate clinical research on diseases affecting bone metabolism during pregnancy. Methods. We surveyed 120 low-risk pregnant women attending routine antenatal care from January 2020 to March 2020. The serum levels of procollagen type I N-propeptide (PINP), N-terminal osteocalcin (N-MID), and C-terminal telopeptide of type I collagen (β-CTX) were measured in the first trimester (<13 weeks), second trimester (14–27 weeks), and third trimester (>28 weeks). Reference intervals for BTMs during pregnancy were analyzed. The Kruskal–Wallis test and paired t-test are used to analyze differences between groups. Spearman correlation coefficients expressed the measure of linear association. Results. The bone resorption marker β-CTX in third trimester increases compared to the first trimester and the second trimester (P < 0.001, P < 0.001). The bone formation markers PINP and N-MID were decreased from the first trimester to the second trimester (P = 0.01, P < 0.001) and then raised from the second trimester to the third trimester (P < 0.001, P < 0.001). Two indices of bone turnover rate, β-CTX/PINP and β-CTX/N-MID, were increased from the first trimester to the second trimester (P < 0.001, P < 0.001) and then decreased from the second trimester to the third trimester (P = 0.02, P < 0.001). Conclusion. This study established reference intervals for BTMs in pregnant women and observed the changes in BTMs during the different trimesters of pregnancy. The present findings can help in clinical monitoring of the effects of pregnancy diseases on the bone metabolism of pregnant women.